Significance of Global Public Goods in the Light of Increasing Global Risks - Nikolova, Velichka (Research Papers, 2024)
The present article focuses on the role of global public goods in the light of a dynamically changing global environment. To this end, attention is first paid to the main features of this type of goods and the challenges associated with providing financial resources for their production, followed by some more specific examples of global public goods, which are considered taking into account the danger of global risks.